FEATURES OF REGIONAL INNOVATION POLICY IN BUILDING A MODEL OF SUSTAINABLE DEVELOPMENT OF THE TERRITORIES - Vladimir N. Kruglov; Sergei A. Orekhov (Статистика и экономика)
The relevance of the article is determined bythe need for innovative development of thedomestic economy. Existing tools, methods and models are constantly evolving, being inunceasing dynamics. This is what makes youlearn and adopt the best practices of thoseregions, which have achieved in this directionthe most progress. And it is to such entities of the Russian Federation is the Kaluga region.Here in recent years managed to achievesustainable growth development areas onthe innovation platform, which is the subjectof analysis of this article.